Smith & Tanagho's General Urology - McAninch, J. W. Jack W; Lue, T. F. Tom F (A LANGE medical book, 2013)
The definitive guide to understanding, diagnosing, and treating urologic disorders - completely updated with the latest clinical developments. Smith & Tanagho's General Urology, 18th edition offers a complete overview of the diagnosis and treatment of the diseases and disorders managed by urologic surgeons. This trusted classic delivers a clear, concise presentation of the etiology, pathogenesis, clinical findings, differential diagnosis, and medical and surgical treatment of all major urologic conditions. The well-organized, user-friendly design makes relevant clinical information and management guidelines easy to find and simple to implement.